Cover Feature: Rapid Synthesis of Fused Polycyclic Heteroaromatics through Successive Vinylic/Aromatic C−F Bond Activation (Eur. J. Org. Chem. 37/2022). Issue 37 (6th September 2022) - Fujita, Takeshi; Fukuda, Takuya; Suzuki, Naoto; Ichikawa, Junji
Abstract : The Cover Feature illustrates the synthesis of fused polycyclic heteroaromatics through successive vinylic/aromatic C−F bond activation. Herein, the sequence of the cleavage of one C−Br/two C−F bonds and the formation of two C−C/one C−O(N) bonds is depicted as a frog hopping on lotus leaves on a pond. More information can be found in the Research Article by T. Fujita, J. Ichikawa et al.